Growth rate of small pancreatic neuroendocrine tumors in multiple endocrine neoplasia type 1: results from an endoscopic ultrasound based cohort study - Kappelle, Wouter F. W.; Valk, Gerlof D.; Leenders, Max; Moons, Leon M. G.; Bogte, Auke; Siersema, Peter D.; Vleggaar, Frank P. (Endoscopy, 2017)
Background and aims In multiple endocrine neoplasia type 1 (MEN1), endoscopic ultrasound (EUS) is used for identification and follow-up of pancreatic neuroendocrine tumors (PNETs). The role of EUS in surveillance of small ( < 20 mm) PNETs is unclear, mostly because the natural course of these lesions is largely unknown. We aimed to determine annual growth and incidence rate of small PNETs in patients with MEN1 using EUS-based surveillance. Patients and methods Linear array EUS procedures in patients with MEN1 between 2002 and 2015 were identified. Number, size, and location of PNETs were recorded. Annual growth of PNETs < 20 mm identified at the initial EUS (“prevalent” PNETs) and during follow-up (“incident” PNETs) was calculated using mixed model linear regression analysis.Results A total of 54 patients were identified and 38 patients were included. In all, 226 PNETs were identified (median size 5.0 mm, interquartile range 3.7 – 7.5) of which 124 (55 %) were prevalent and 102 (45 %) were incident PNETs. Annual incidence rate was 0.79 PNETs/year (95 % confidence interval [CI] 0.73 to 0.87). Overall growth rate was 0.10 mm/year (95 %CI 0.02 to 0.19; P = 0.01); PNETs < 10 mm (n = 198) did not grow (P = 0.23), whereas PNETs ≥ 10 mm (n = 28) grew 0.44 mm/year (95 %CI 0.10 to 0.78; P = 0.01). Prevalent PNETs grew 0.21 mm/year (95 %CI 0.10 – 0.32; P < 0.001), whereas incident PNETs did not grow (P = 0.26). Conclusions The annual growth rate of small, solid PNETs in patients with MEN1 is lower than previously thought. Surveillance intervals could probably be prolonged without compromising safety.